2015
DOI: 10.14742/ajet.1240
|View full text |Cite
|
Sign up to set email alerts
|

ICT Use in Science and Mathematics Teacher Education in Tanzania: Developing Technological Pedagogical Content Knowledge

Abstract: Currently, teacher education colleges in Tanzania are being equipped with computers to prepare teachers who can integrate technology in teaching. Despite these efforts, teachers are not embracing the use of technology in their teaching. This study adopted Technological Pedagogical Content Knowledge (TPACK) as a framework for describing the knowledge and skills that pre-service teachers need to develop in order to effectively integrate technology in science and mathematics teaching. Pre-service teachers (N=22) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 24 publications
2
61
0
3
Order By: Relevance
“…Kafyulilo et al (2015) reported that despite efforts, teachers are slow in embracing technology. His team studied perceived knowledge and skills of integrating technology with the use of TPACK framework and found that more staff development programs are needed to develop technological pedagogical knowledge.…”
Section: International Investigationsmentioning
confidence: 99%
“…Kafyulilo et al (2015) reported that despite efforts, teachers are slow in embracing technology. His team studied perceived knowledge and skills of integrating technology with the use of TPACK framework and found that more staff development programs are needed to develop technological pedagogical knowledge.…”
Section: International Investigationsmentioning
confidence: 99%
“…Several projects were initiated to enhance teachers' pedagogical content knowledge and teaching approaches (Kitta, 2004), and providing schools with adequate teaching and learning resources (Sumra & Katabaro, 2014). Other initiatives include training of more mathematics teachers, and the introduction of Information and Communication Technology (ICT) in teacher education and secondary schools in early 2002 (Kafyulilo, Fisser, Pieters, & Voogt, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In support of the ICT-TPD policy three small scale intervention studies were conducted in the 2010 to 2012 timeframe, in which a professional development program was designed and evaluated (Kafyulilo 2013;Kafyulilo et al 2014Kafyulilo et al , 2015. The studies adopted the collaborative design of technology-enhanced science and mathematics lessons in teacher teams, as an approach for teachers' professional development.…”
Section: Introductionmentioning
confidence: 99%
“…The professional development program aimed at developing technology integration knowledge and skills for science and mathematics pre-service teachers, who were college students (study 1, Spring 2010) (Kafyulilo et al 2015) and in-service teachers or practicing teachers, conducted with teachers from a school which is nicknamed as school A (study 2, Spring 2011, Kafyulilo et al 2014). Study 3 was conducted with practicing teachers from two schools nicknamed as school B and C. (Spring 2012) (Kafyulilo 2013).…”
Section: Introductionmentioning
confidence: 99%